(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2010)
From a concern with the scientific standing of phenomenology, Giorgi (2010) criticizes two forms of phenomenological practice: interpretative phenomenological analysis (IPA) and the approach of Collaizzi, along with three doctoral dissertations. In this paper I will respond to the critique of IPA presented by Giorgi.